Exploring 3-hydroxyflavone scaffolds as mushroom tyrosinase inhibitors: synthesis, X-ray crystallography, antimicrobial, fluorescence behaviour, structure-activity relationship and molecular modelling studies. Issue 18 (12th December 2021) - Ashraf, Jamshaid; Mughal, Ehsan Ullah; Sadiq, Amina; Bibi, Maryam; Naeem, Nafeesa; Ali, Anser; Massadaq, Anam; Fatima, Nighat; Javid, Asif; Zafar, Muhammad Naveed; Khan, Bilal Ahmad; Nazar, Muhammad Faizan; et al.
Abstract: To explore new scaffolds as tyrosinase enzyme inhibitors remain an interesting goal in the drug discovery and development. In due course and our approach to synthesize bioactive compounds, a series of varyingly substituted 3-hydroxyflavone derivatives (1-23 ) were synthesized in one-pot reaction and screened for in vitro against mushroom tyrosinase enzyme. The structures of newly synthesized compounds were unambiguously corroborated by usual spectroscopic techniques (FTIR, UV-Vis, 1 H-, 13 C-NMR) and mass spectrometry (EI-MS). The structure of compound 15 was also characterized by X-ray diffraction analysis. Furthermore, the synthesized compounds (1-23 ) were evaluated for their antimicrobial potential. Biological studies exhibit pretty good activity against most of the bacterial-fungal strains and their activity is comparable to those of commercially available antibiotics i.e. Cefixime and Clotrimazole. Amongst the series, the compounds 2, 4, 5, 6, 7, 10, 11, 14 and 22 exhibited excellent inhibitory activity against tyrosinase, even better than standard compound. Remarkably, the compound 2 (IC50 = 0.280 ± 0.010 μg/ml) was found almost sixfold and derivative 5 (IC50 = 0.230 ± 0.020 μg/ml) about sevenfold more active as compared to standard Kojic acid (IC50 =1.79 ± 0.6 μg/ml). Moreover, these synthetic compounds (1-23 ) displayed good to moderate activities against tested bacterial and fungal strains. Their emission behavior was also investigated in order to know their potential as fluorescent probes. The molecular modelling simulations were also performed to explore their binding interactions with active sites of the tyrosinase enzyme. Limited structure-activity relationship was established to design and develop new tyrosinase inhibitors by employing 2-arylchromone as a structural core in the future. Communicated by Ramaswamy H. Sarma